The introduction of multi-strain probiotics to preterm infants in a regional hospital: an observational study - Abrahams, Meliza (Department of Paediatrics and Child Health, 2025)
Background: Worldwide 1 in 10 of all infants are born preterm. Late onset sepsis (LOS) (>3days of life) and necrotising enterocolitis (NEC) are important causes of morbidity and mortality in this vulnerable group. Probiotics may help to decrease the incidence of these conditions, although controversies remain. Objectives: To describe the implementation of multi-strain probiotics in George Hospital (GH) and determine the incidence of NEC, LOS and mortality in this group. Also, to compare with previous years where there were either no probiotics or only single strain probiotics. Methods: A retrospective observational study was conducted between February 2019 to July 2020 at George Hospital, Western-Cape, South-Africa. Data were collected from infants who weighed between 800g to 1200g to observe the occurrence of LOS and NEC. Results: Seventy-seven inborn infants were included. They had a median weight of 1000g, IQR [900- 1120g] and a median gestation of 30weeks, IQR [28-31weeks]. The ratio of male to female was 51:49. All of them received breastmilk. A total of eleven (14.3%) infants had positive cultures. These were predominantly gram-negative organisms and there were no positive cultures of probiotic organisms. Seventy five percent of the infections occurred in ELBW infants and their risk for mortality is higher overall. There was a total of seven deaths (9%) of which 3 were before 72hours of life. Out of all the 77 infants 4 died of LOS. None of the infants in the group had clinical or radiological NEC. Compared with the previous time periods, there was a similar rate of LOS, but a reduction of NEC and death. Conclusion: The introduction of probiotics to a regional hospital is possible. Less NEC was observed during the administration of multi-strain probiotics